Histiocytic sarcoma of the stifle in a dog with cranial cruciate ligament failure and TPLO treatment - Harasen, G. L. G.; Simko, E. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
A 10-year-old spayed female Golden Retriever was admitted with chronic lameness of the right hind limb. A tibial plateau leveling osteotomy (TPLO) had been performed on this leg approximately three years previously. A progressively growing soft tissue mass, affecting the right stifle, previously treated with TPLO was biopsied and found to be a histiocytic sarcoma. Previously proposed links between the development of neoplasia in the stifle region and the presence of chronic synovitis, osteotomy, orthopaedic implants, and specifically the Slocum TPLO plate, are briefly discussed.
Keywords: Histiocytic sarcoma; TPLO